PIDANA PENGAWASAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DALAM SISTEM PEMIDANAAN DI INDONESIA - I Putu Suwarsa (University of Udayana, 2013)
ABSTRACTThis research was conducted with the normative approach legislation. Factualapproach, analytical approach to the legal concept of a comparative approach in thecriminal judicial oversight of Children in Conflict with the Law in the criminal sistem inIndonesia.In formulating criminal law criminal policy oversight of Children in Conflict withthe Law in the guidance sistem of positive law in Indonesia, consists of 3 major topics:First, the substance of Children in Conflict with the Law into law in Indonesia, Second,Determination of sanctions / penalties against Children in Conflict with the Law inIndonesia's criminal law policy, Third, criminal oversight of Children in Conflict with theLaw and its relevance to the theory of punishment in modern criminal law in Indonesia.Criminal oversight of Children in Conflict with the Law as the integrative goals ofpunishment in accordance with the ideas and correctional sistem discussed 3 subjectsnamely: First, criminal oversight of anal naughty review of aspects of the integrativetheory of punishment, Second, Criminal oversight of Children in Conflict with the Lawreview of aspects of correctional sistem, Third, Criminal oversight of Children in Conflictwith the Law in terms of aspects of legal protection and benefit of the criminal lawrequirement for social welfare (children). And its application by all law enforcementcomponents and related institutions involved in handling cases of children in conflict withthe law in coaching children in prison.